The Effect of Surgery on Cord Vibration in Patients with Vocal Cord Polyps: Retrospective Videolaryngostroboscopy Study - Özgür Pınarbaşlı, Mehmet; Alaiye, Ali; Turan, Şükrü; Halit Aydın, Ahmet; Uzun, Tankut; Kaya, Ercan; Kezban Gürbüz, Melek (ENT Updates, 2019)
Objective: Vocal cord polyps are benign lesions of the larynx that are frequently seen and are treated surgically. These lesions generally develop in the free edge of the vocal cords, and form an incomplete glottal closure accompanied by irregular vibration of the vocal cords. In this study, the aim is to investigate the effect of surgery on vocal cord vibration in patients with vocal cord polyps who are treated with the endolaryngeal cold knife microsurgery. Method: Patients treated with endolaryngeal microsurgery at our clinic between 2014 and 2016, who were reported as vocal cord polyps by postoperative pathology result, and who regularly coming for follow-up examinations were included in the study. Using a scale which was first described by Hirano and Bless and modified and confirmed to be reliable in a study performed by Gürbüz et al., the preoperative and postoperative second month images of the patients were statistically compared. Results: 10 of the 25 patients included in our study were female (40%) and 15 were male (60%). In all patients, vocal cord polyps were unilateral, and were located in anterior 1/3 of the vocal cord in 12 patients (48%), and in medial 1/3 of the vocal cord in 9 patients (36%). It was determined that impaired vocal cord vibratory functions showed statistically significant recovery in the postoperative period compared to the preoperative period (p<0.05). Conclusion: Successful endolaryngeal cold knife microsurgery excision can correct impaired vibratory functions of vocal cords in patients with vocal cord polyps.